Influences on financial statement integrity: the role of intellectual capital, independent commissioners, and gender diversity - Leny Suzan; Fadiyah Beliacintiana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aimed to determined the impact of intellectual capital, independent commissioners, gender diversity, and financial statement integrity in property and real estate subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. In today's rapidly evolving business landscape, the urgency of leveraging intellectual capital is paramount for fostering innovation and driving sustainable growth. Financial statement integrity in this study was measured using market to book value (MBV). The population included property and real estate companies listed on the IDX for the period 2019-2023. Purposive sampling was used to select 8 companies meeting the criteria, providing a total of 40 observation data points. Panel data regression analysis was performed using E-views 12. Results indicate that intellectual capital, independent commissioners, and gender diversity had a simultaneous effect on financial statement integrity. However, intellectual capital and independent commissioners did not affect financial statement integrity, while gender diversity had a negative impact on financial statement integrity. Property and real estate companies should enhance financial statement integrity to increase investor confidence, strengthen market reputation, and gain sustained competitive advantage.